قياس جودة الخدمة في القطاع المصرفي السوري دراسة ميدانية مقارنة بين المصارف الخاصة والعامة - حموي, فواز; إسماعيل, محمد (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهدف البحث إلى تقييم جودة الخدمات التي تقدمها المصارف السورية الخاصة والعامة, والمقارنة بينها, وتحديد أوجه الاختلاف في مستوى الجودة المدركة من وجهة نظر العملاء, وذلك باستخدام مقياس أداء الخدمة SERVPERF لقياس جودة الخدمة المدركة. تم جمع بيانات البحث باستخدام استبيان, حيث تم توزيع (131) استبانة, وبلغ عدد الاستبيانات المسترجعة والصالحة للتحليل (117), أي ما نسبته (89%) وهي نسبة جيدة للتحليل. أظهرت الدراسة وجود علاقة ارتباط قوية وتأثير لأبعاد جودة الخدمة الخمسة على الجودة الكلية، والتي تمثل رضا العملاء عن جودة للخدمة المقدمة في المصارف السورية الخاصة والعامة, ووجود فروق ذات دلالة معنوية بين متوسط استجابات عملاء المصارف العامة والخاصة بالنسبة لكافة أبعاد الجودة، باستثناء بعد التعاطف. كما أظهرت الدراسة إن درجة رضا العملاء عن مستوى جودة الخدمة المقدمة في المصارف الخاصة أكبر منها في المصارف العامة. أوصت الدراسة بضرورة الاهتمام بتحسين مستوى الجودة في المصارف السورية, لاسيما العامة منها, من خلال التركيز بدرجة اكبر على بعد التعاطف والملموسة لجودة الخدمة, والاهتمام بتدريب الموظفين وتأهيلهم, واعتماد الجودة معياراً أساسياً للعمل. This paper aims to assess the service quality provided by private and public banks in Syria. It also aims to compare and specify differences between these banks at the level of recognized quality from the customers' point of view. This is achieved by concentrating on the service performance (SERVPERE) to measure the recognized service quality. The data for this research were collected using a questionnaire. 131 had been distributed. 117 were returned, which amounts for 89% of the distributed questionnaires. The results had shown a strong correlation and effect of service quality dimensions on total service quality which represented customers' satisfaction on services quality provided in Syrian private and public banks, and there are significant differences between the customers' response means in public and private banks in relation to all quality dimensions except for the dimension of empathy. The study also showed that the degree of customers' satisfaction with the level of the services quality provided in private banks outclasses its counterparts. The research recommends better attention with improving the level of quality in Syrian banks, especially public ones, through more concentration on the empathy and intangible dimensions of service quality, and paying better attention to employee training and qualification, as well as adopting quality as an essential criterion work.